LINE-2 transposable elements are a source of functional human microRNAs and target sites - Petri, Rebecca (PLoS Genet, 2019)
Transposable elements (TEs) are dynamically expressed at high levels in multiple human tissues, but the function of TE-derived transcripts remains largely unknown. In this study, we identify numerous TE-derived microRNAs (miRNAs) by conducting Argonaute2 RNA immunoprecipitation followed by small RNA sequencing (AGO2 RIP-seq) on human brain tissue. Many of these miRNAs originated from LINE-2 (L2) elements, which entered the human genome around 100–300 million years ago. L2-miRNAs derived from the 3’ end of the L2 consensus sequence and thus shared very similar sequences, indicating that L2-miRNAs could target transcripts with L2s in their 3’UTR. In line with this, many protein-coding genes carried fragments of L2-derived sequences in their 3’UTR: these sequences served as target sites for L2-miRNAs. L2-miRNAs and their targets were generally ubiquitously expressed at low levels in multiple human tissues, suggesting a role for this network in buffering transcriptional levels of housekeeping genes. In addition, we also found evidence that this network is perturbed in glioblastoma. In summary, our findings uncover a TE-based post-transcriptional network that shapes transcriptional regulation in human cells.